(3GdCMGOjK GdeNJGQIs - (3eMeO Hf YHO GdhGMO Hf CMeO Hf YHO GdQMef GdSYOj GdebOSj, VjGA GdOjf CHh YHO Gddg,J (B643 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3Cfg SeY GHf YHGS jbhd OYG QLd QLdkG abGd (B" (3jG GHG GdbGSe aGQJGY dgG GdfHi Udi Gddg Ydjg hSde abGd QLd jG QShd Gddg Efi de CYfc YfjJ ZjQc abGd GdfHi Udi Gddg Ydjg hSde(B( (3JSehG HGSei hdG JcfhG HcfjJi (B) s
(3BNQgG (B:s
(3hSeY KdGK hQbGJ ef BNQ GdLRA hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3YdjgG SeGYGJs
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B263s
Keywords: (3GdMOjK h GdeUWdMs